Effectiveness of residual spraying of peridomestic ecotopes with deltamethrin and permethrin on Triatoma infestans in rural western Argentina: a district-wide randomized trial - Gürtler Ricardo E.; Canale Delmi M.; Spillmann Cynthia; Stariolo Raúl; Salomón Oscar D.; Blanco Sonia; Segura Elsa L. (The World Health Organization, 2004)
OBJECTIVE: To compare the effectiveness of a single residual spraying of pyrethroids on the occurrence and abundance of Triatoma infestans in peridomestic ecotopes in rural La Rioja. METHODS: A total of 667 (32.8%) peridomestic sites positive for T. infestans in May 1999 were randomly assigned to treatment within each village, sprayed in December 1999, and reinspected in December 2000. Treatments included 2.5% suspension concentrate (SC) deltamethrin in water at 25 mg active ingredient (a.i.)/m² applied with: (a) manual compression sprayers (standard treatment) or (b) power sprayers; (c) 1.5% emulsifiable concentrate (EC) deltamethrin at 25 mg a.i./m²; and (d) 10% EC cis-permethrin at 170 mg a.i./m². EC pyrethroids were diluted in soybean oil and applied with power sprayers. All habitations were sprayed with the standard treatment. FINDINGS: The prevalence of T. infestans 1-year post-spraying was significantly lower in sites treated with SC deltamethrin applied with manual (24%) or power sprayers (31%) than in sites treated with EC deltamethrin (40%) or EC permethrin (53%). The relative odds of infestation and catch of T. infestans 1-year post-spraying significantly increased with the use of EC pyrethroids, the abundance of bugs per site before spraying, total surface, and host numbers. All insecticides had poor residual effects on wooden posts. CONCLUSION: Most of the infestations probably originated from triatomines that survived exposure to insecticides at each site. Despite the standard treatment proving to be the most effective, the current tactics and procedures fail to eliminate peridomestic populations of T. infestans in semiarid rural areas and need to be revised.